Cloud Intrusion Detection System - Norli, Muhammad Hanis; Mahari, Mardiana (Journal of Computing Technologies and Creative Content, 2019)
Issue of security is very paramount in any organization, especially organization that has confidential data. Therefore, this project intends to aid in security of the company by introducing intrusion detection system to the cloud service. This project is not just the normal intrusion detection system that only detect malicious packet in the network, it is a project that has notification alert to users. By this, the users will receive notification in the router interface which is installed in the router. With the help of IDS, notification will be prompt to the users of any malicious attacks that are happening to their system.